THE LEGAL UTILITARIANISM APPROACH IN THE REGULATION OF AGE VERIFICATION FOR FINTECH USERS: CASE DATA ANALYSIS AND STUDY ON UNDERAGE MISUSE BASED ON INDONESIAN REGULATION - Aditya Nur Tio Sanda; Rahmatullah Ayu Hasmiati; Surahman; M. Nurcholis Alhadi (Sekolah Tinggi Ilmu Hukum Awang Long, 2026)
The rapid growth of financial technology, fintech in Indonesia has brought significant benefits in expanding financial inclusion, particularly for communities underserved by traditional banking. However, this progress also presents serious challenges, especially regarding user age verification. The ease of registering with only an uploaded ID card and selfie has enabled minors to misuse their parents' identities to access online loans or pay later services, resulting in financial, psychological, and legal risks for families and fintech providers. Through the legal utilitarianism perspective, strict age verification is seen as a policy that produces the greatest benefit for society by reducing identity misuse, minimizing default risk, and strengthening public trust in the digital ecosystem. Challenges such as cybersecurity, data leakage, weak internal supervision, and illegal fintech proliferation indicate the need for integrated biometric systems, validation with the national population database, Dukcapil, and digital literacy within families. Therefore, strengthening the legal framework for age verification becomes an essential foundation toward a safe, inclusive, and socially beneficial fintech industry.